TINGKAT PENERIMAAN DAN PENGGUNAAN SISTEM INFORMASI MANAJEMEN PUSKESMAS KABUPATEN JEMBER - Sedyo Pinerdi; Efri Tri Ardianto; Novita Nuraini; Ida Nurmawati (Politeknik Negeri Jember, 2020)
The district health office of Jember conducted a trial of operating SIMPUS in 20 puskesmas, but only 16puskesmas operated the SIMPUS. The district health office of Jember will be announced at the end of 2019SIMPUS will be fully operated in 50 puskesmas throughout the Jember district. This study is aimed to describethe level of acceptance and use of the Puskesmas management information system using the Theory ofAcceptance and Use of Technology (UTAUT) method. This study discusses the variables of performanceexpectancy, effort expectancy, sosial influence, facilitating conditions, behavioral intention, and the usebehavioral of SIMPUS users that are spread across 16 public health platforms in the District Health Office ofJember. This type of research is observational descriptive. The data analysis technique used is descriptive.The results of this study were that the officers were quite confident that they would get ease while workingusing SIMPUS (55.9%), the work became easy when the officers used SIMPUS (69.5%), the head of thepuskesmas and health offices supported the use of SIMPUS (73,7%), the facilities and infrastructure providedcan support the use of SIMPUS (58.5%), officers wish to use SIMPUS in the near future (70.3%), and officersuse SIMPUS when working (65.3%). The district health office of Jember needs to operate SIMPUS again andincrease server capacity so that the acceptance and use of SIMPUS increases.